If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + -1ln(4) = 0 Multiply ln * x lnx + -1ln(4) = 0 Reorder the terms for easier multiplication: lnx + -1 * 4ln = 0 Multiply -1 * 4 lnx + -4ln = 0 Reorder the terms: -4ln + lnx = 0 Solving -4ln + lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-4 + x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-4 + x)' equal to zero and attempt to solve: Simplifying -4 + x = 0 Solving -4 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + x = 0 + 4 x = 0 + 4 Combine like terms: 0 + 4 = 4 x = 4 Add '-1x' to each side of the equation. x + -1x = 4 + -1x Combine like terms: x + -1x = 0 0 = 4 + -1x Simplifying 0 = 4 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (7+5x)-5x= | | ln(x)-on(4)=0 | | -25=5(3g+4) | | (9x+10)+(13-9x)= | | 3x^2-2y^2=1 | | z-38=-28 | | 12(5x+9)-11x= | | 25x+7(1.50)=10 | | X^5x=6 | | 5-5x-x=53 | | -1+5x-7x=3 | | 8.4254+.6018R=R | | 6(x+2)=5(x+4) | | 9x^4-19x^2-2=0 | | -3+x=6n+22 | | -30x+12(x-1)=24x+200 | | 5x-y=30(3) | | 5a-5ab= | | 2x=x+14x | | A^2+11a=-30 | | 3+0.4n= | | -11+51=-4(x+5) | | -30x+12(x-1)=24x+2 | | 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n | | 9(3x-5)+9x= | | 3(x-4)=23-4c | | 3lnc=2lny | | 6+6x-2x=-10 | | 25t^2+45t=0 | | 5log(5x-10)=15 |